On the order of relative approximation of classes of differentiable periodic functions by splines - Babenko, V. F.; Parfinovych, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
In the case where $n → ∞$, we obtain order equalities for the best $L_q$ -approximations of the classes $W_p^r ,\; 1 ≤ q ≤ p ≤ 2$, of differentiable periodical functions by splines from these classes.